Introduction to electrical power system technology - Bosela, Theodore R. (Prentice Hall, 1997)
"Introduction to Electrical Power System Technology provides the reader with an insight into some of the principles and practices of electrical utility engineering. The author has emphasized an applications-oriented approach to the topics covered. Although primarily written for senior-level electrical engineering technology students, the text is suitable for electrical engineering students as well."--BOOK JACKET.